Opening Pandora’s Molecular Box - Ebach, Malte C.; de Carvalho, Marcelo R.; Williams, David M. (Zootaxa, 2011)
Mooi & Gill (2010) have prised open the cap of the molecular systematics vial and caused a debate to take-off in the ichthyological community. Molecular trees and their supporting evidence are the first two items to leave this Pandora’s box, closely followed by DNA barcoding and DNA taxonomy. In short, the debate is fuelled by the nature of molecular data: can nucleotide sequences provide the necessary evidence for relationship? The majority (Wiley et al., 2011) believe that DNA contains informative data; however, in our view, they have failed to ascertain the truth of their claim. Not all data are informative. Data may provide supporting evidence, conflicting evidence, or no evidence at all. Assuming that all data are informative apriori to analysis is a theoretical position, not an empirical one. We claim that systematics is, quite the contrary, empirical, and relies on evidence rather than on implicit measurements of data. Consequently, this assertion leads back to the original question of evidence in molecular systematics, namely molecular homology.